Model Pengelolaan Waqaf dalam Keragamaan Etnis di Aceh - Husni; Juliana Putri; Harjoni (Politeknik Ganesha Medan, 2023)
The purpose of this study is first, to explain the perceptions of the Gayo and Pesisir tribes towards waqf management. Second, it describes the waqf management model carried out by the Gayo tribe and the Aceh Coastal tribe in their respective regions. And third, providing ideas, concepts, and ideal practices in waqf management in Aceh. The research method used is the descriptive qualitative research method. The results showed that the majority of the people of Lhokseumawe City gave land waqf for places of worship and education, while the people of Central Aceh or the Gayo tribe had a tradition of using waqf for the common good of their ancestors, namely Livestock Locations (Peruweren), Uber-Uber and Blang Paku and ulu ni wih area (upstream water area). The waqf management model carried out by the Gayo tribe and the Aceh Coastal tribe in their area is still mostly carried out for religious purposes such as; the construction of places of worship (mosques, madrasahs, and study rooms or Islamic boarding schools), and most of them are used for public cemeteries and the people of Aceh, especially Central Aceh and Lhokseumawe, are also still taboo about waqf assets outside of immovable waqf such as cash waqf. Ideal management of waqf for districts/cities in Aceh that is capable of providing economic influence can be carried out with seven precise steps, namely Compilation of the Waqf Program; Empowerment of Waqf Assets; Waqf Assets Certification; Nazir Empowerment; Financial Reports and Management Systems; Government Integration; and Nazir Integration